The Influence of Leadership Style and Compensation on Employee Performance - Tri Kurniawan; Supartini; Novelia Asita Mranani (Journal of Economy, Accounting and Management Science (JEAMS), 2024)
Good human resources will drive the company to progress and develop. Human resources are the main factor affecting company performance. Companies with superior human resources will be able to properly organize every activity within the company, employees will be able to work optimally and the results achieved will be in accordance with predetermined standards. The purpose of this study is to determine the effect of leadership style and compensation simultaneously and partially on the performance of employees at Tanjung Kodok Lamongan Beach Resort Hotel. The sample of this research is the employees of Hotel Beach Resort Tanjung Kodok Lamongan, with a total sample of 50 respondents. The analysis technique uses Multiple Linear Regression with the SPSS program or software. The results showed that simultaneously (simultaneous) showed that leadership style and compensation had an effect on employee performance, partially leadership style had a positive and significant influence on employee performance, and compensation had a positive and significant effect on employee performance.